ANALYSIS OF WRITING MATERIAL IN ENGLISH TEXTBOOK FOR THE FIRST GRADE SENIOR HIGH SCHOOL - Dervine Hutagalung Hutagalung (LP4MK STKIP PGRI Lubuklinggau, 2020)
Texbook is an important references employed by teachers and students in the learning process. It is supported by Grand as cited in Kayapinar, 2013 states that coursebook try to solve the problem by creating opportunities for learners to use target in the classroom. Considering such situations, an evaluation of existing materials is necessary to reveal the weakness of the textbook and improve in strength Cunningsworth (1995). This study aims to analysis the presentation, and linguistic elements. This study is descriptive qualitative employing a concent analysis. A checklist for evaluation was developed based on criteria proposal by BNSP and Cunningsworth (1995). The findings showed that in terms of writing materials presentation, all of the writing tasks are in the forms of guided writing, in which students are tasked to write responses, in restricted length, to the given prompts. In terms of linguistics elements, they are treated in integrated manner in the textbook. This study indicates that writing tasks in the textbook have been proportionally covered. The findings suggest that independent references for vocabulary and grammar items are necessary for self-study. The topics should be more various as well to provide students with wider chances to get exposed to different contexts.